SOCIAL ISSUES AND ENVIRONMENT: सामाजिक मुद्दे एवं पर्यावरण - Tiwari, Aarti (International Journal of Research -GRANTHAALAYAH, 2015)
Man is born with his environment. And lives among them. In other words, the whole society lives among the environment, that is, in the lap of nature. But for this life, man mainly depends on environment. In order to keep his life running smoothly and to make it better, man constantly tries and for this he exploits natural resources. In this way, man has continued his life from natural resources till today. Due to which there is some damage to nature. Because man has used such chemicals in the blindness of modernity. Which is extremely harmful for nature. Now the question arises whether humans stop their development. No, he can continue his development without harming nature or the environment. It is just a matter of necessity that whatever he does should not harm the environment because if that damage is causing harm to the environment. So man is doing his own loss indirectly. Global warming and ozone depleting greenhouse effect, etc. are examples that directly illustrate the harm caused by humans to the environment. मनुष्य अपने पर्यावरण के साथ ही जन्म लेता है। और उसके बीच ही अपना जीवन यापन करता है। दूसरे शब्दों में सारा समाज पर्यावरण के बीच अर्थात प्रकृति की गोद में अपना जीवन यापन करता है। किन्तु इस जीवनयापन के लिए मनुष्य मुख्य रूप से पर्यावरण पर निर्भर करता है। अपने जीवन को सुचारू रूप से चलाए रखने एवं उसे और अधिक बेहतर बनाने के लिए मनुष्य निरंतर प्रयास करता है तथा इसके लिए वह प्राकृतिक संसाधनों का दोहन करता है। इस प्रकार मनुष्य आदिम युग से आज तक निरंतर प्रकृतिक संसाधनों से अपना जीवन चलाता आया है। जिससे प्रकृति को कुछ नुकसान भी पहुंचा है। क्योंकि मनुष्य ने आधुनिकता की अंधीदौड में ऐसे रसायनों का प्रयोग किया है। जो प्रकृति के लिए अत्यंत नुकसानदेह है। अब प्रश्न यह उठता है कि क्या मनुष्य अपना विकास बंद करदे। नहीं वह अपना विकास बिना प्रकृति या पर्यावरण को नुकसान पहुंचाए भी जारी रख सकता है। बस आवश्यकता है तो इस बात की कि वह जो भी करे उससे पर्यावरण को नुकसान न पहुंचे क्योंकि यदि वह नुकसान पर्यावरण को पहुंचा रहा है। तो परोक्ष रूप से मनुष्य अपना नुकसान स्वयं कर रहा है। वैश्विक तापवृद्धि एवं ओजोनक्षरण ग्रीनहाउस प्रभाव बढ़ना इत्यादि ऐसे उदाहरण हैं जो मानव द्वारा पर्यावरण को पहुंचाए जा रहे नुकसानों को प्रत्यक्ष रूप से बयान करते हैं।